Il perduto soffitto ligneo del cardinale Niccolò Gaddi per la Cattedrale di Cosenza (1545-1547) - Mussari, Bruno (Opus Incertum, 2018)
Niccolò Gaddi (1527-1552), Florentine Cardinal, archbishop of Cosenza from 1528 to 1535 and administrator of the diocese of Calabria until 1549, commissioned Bartolomeo della Scala of Pietrasanta with the construction of a wooden coffered ceiling for the Cathedral of Cosenza. An 18thcentury manuscript chronicle and some notarial acts of 1545 and 1546 document that he was already active in Calabria in those years. The coffered ceiling no longer exists, but this paper proposes a possible reconstructed configuration, based on the description contained in the assignment document. It was to be based on some famous Florentine and Roman examples, dating back to the second half of the 15th century, which were certainly known to the stonemasons and workers involved. The wooden coffered ceiling of Cosenza is the first known in Calabria, and thus it can be considered as the local reference for subsequent regional applications. It is also witness to the spread of the forms and architectural languages of the Renaissance in Calabria, introduced by a sophisticated commission and expert Tuscan craftsmen, whose presence was due to the widespread phenomenon of migratory flows of workers.